Development of an Optimization Method for Locating the Pelvis in an Automobile Seat - Park, Jangwoon; Ebert, Sheila M.; Reed, Matthew P.; Hallman, Jason J. (Procedia manufacturing, 2015)
The position and orientation of a vehicle occupant's pelvis are important for seat design and the provision of safety belts. However, the direct measurement of pelvis location in a vehicle seat is difficult due to interference from the vehicle and its seat structure, as well as driver factors such as abdomen adiposity. An optimization method was developed to locate the driver's pelvis based on the kinematic relationships between the pelvis bony landmarks, body landmarks, and skeletal joint locations measured in a laboratory “hardseat” that allows access to posterior landmarks. The method accounts for variation in flesh margins at pelvis landmarks. Body landmark locations were measured using a coordinate measurement machine for 90 men and women in the hardseat and a vehicle seat set to 9 driver package conditions. Pelvis locations in the vehicle seat were calculated using two supra-patella landmarks, anterior-superior iliac spines (ASIS) surface landmarks, and L5/S1 joint location along with the pelvis kinematic linkage calculated from the hardseat for each participant. To assess the performance of the method, the intra-subject standard deviations (SD) of each participant's fitted ASIS flesh margins were evaluated. Across the 9 driver package conditions, the mean intra-subject SD of the fitted ASIS flesh margins were 5.6mm horizontal and 4.7mm vertical.. The new method provides a consistent way to calculate the position and the orientation of the pelvis in which posterior landmarks cannot be directly measured, providing improved accuracy of the pelvis position for a wide range of vehicle, seat, and safety system assessments.